Transient sex-related changes in the mice hypothalamo–pituitary–adrenal (HPA) axis during the acute phase of the inflammatory process - T. Daneva; E. Spinedi; R. Hadid; M.-C. Jacquier; M. Giacomini; R. C. Gaillard (Mediators of Inflammation)
The potential role of endogenous sex hormones in regulating hypothalamo–pituitary–adrenal (HPA) axis function was investigated after a single injection of endotoxin in adult (8 week old) BALB/c mice of both sexes. The effect of LPS on plasma ACTH, corticosterone (B), testosterone and oestradiol (E) levels and on anterior pituitary (AP) ACTH and adrenal B contents at different times after treatment was studied. The results indicate that: (a) basal B but not ACTH plasma levels were significantly higher in female than in male mice; (b) LPS significantly increased both ACTH and B plasma levels over the baseline 2 h after injection, both hormone levels being higher in female than in male mice; (c) although plasma ACTH concentrations recovered the basal value at 72 h after LPS in animals of both sexes, plasma B levels returned to the baseline only at 120 h after treatment; (d) E plasma levels significantly increased 2 h after LPS and returned to the baseline at 72 h post-treatment, in both sexes; (e) at 2 h after LPS, testosterone plasma levels significantly decreased in male mice and increased in female mice, recovering the baseline level at 120 and 72 h after LPS, respectively; (f) AP ACTH content was similar in both sexes in basal condition and it was significantly diminished 72 h post-treatment without sex difference; whereas AP ACTH returned to basal content 120 h after LPS in males, it remained significantly decreased in females; (g) basal adrenal B content was higher in female than in male mice, and it significantly increased in both sexes 2 h post-LPS, maintaining this sex difference. Whereas adrenal B returned to basal content 72 h after treatment in male mice, it remained significantly enhanced up to 120 h post-LPS in female animals. The data demonstrate the existence of a clear sexual dimorphism in basal condition and during the acute phase response as well as in the recovery of the HPA axis function shortly after infection.